2015
DOI: 10.1159/000438707
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Postoperative Intra-Abdominal Abscess after Laparoscopic Appendectomy: Analysis for Consecutive 1,817 Experiences

Abstract: Background: Possible risk factors for postoperative intra-abdominal abscess (IAA) formation after laparoscopic appendectomy (LA) remain controversial. A perforated appendicitis, diabetes mellitus, peritoneal irrigation, obesity and age are considered to be possible risk factors for postoperative IAA, but the existing evidence is insufficient. This study aimed to identify the risk factors for IAA formation in patients receiving LA. Methods: Between January 2010 and December 2013, 1,817 patients who underwent 3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 32 publications
4
56
0
4
Order By: Relevance
“…Previously, it has been reported that a surgical grading system [8] or the intraoperative diagnosis [6910] could predict the development of postoperative infectious complications; however, no recent studies have demonstrated these features in the pathologic diagnosis. As we reported in our recent article [5], the surgical diagnosis of appendicitis alone seems inappropriate for predicting the development of postappendectomy IAA. Rather, the adequacy of intraoperative infectious source control and postoperative antimicrobial treatment were more predictive of the outcome than the gross morphology of appendicitis itself [11].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Previously, it has been reported that a surgical grading system [8] or the intraoperative diagnosis [6910] could predict the development of postoperative infectious complications; however, no recent studies have demonstrated these features in the pathologic diagnosis. As we reported in our recent article [5], the surgical diagnosis of appendicitis alone seems inappropriate for predicting the development of postappendectomy IAA. Rather, the adequacy of intraoperative infectious source control and postoperative antimicrobial treatment were more predictive of the outcome than the gross morphology of appendicitis itself [11].…”
Section: Discussionmentioning
confidence: 96%
“…The details of our protocol have been previously reported [5]. Briefly, appendicitis was diagnosed on the basis of the patients' medical history, physical examinations, and radiological findings.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest predictors of post‐operative SSI were seen in individuals who had an open operation, and those who identified as ATSI. Evidence from multiple studies has demonstrated higher rates of SSI in patients who have an open compared to laparoscopic appendicectomy . Further subgroup analysis in our patient population showed that 69% of the converted to open cases were associated with complicated appendicitis.…”
Section: Discussionmentioning
confidence: 61%
“…[6] The same study reported that the risk factors for intraabdominal abscess formation after laparoscopic appendectomy were peritoneal irrigation and nonplacement of a peritoneal drain. [6] In the present case, peritoneal irrigation (about 100cc) was performed during the laparoscopic appendectomy, and a peritoneal drain was inserted. In the present case, a small intraabdominal abscess was detected in the ileocecum area 2 weeks after the laparoscopic appendectomy was performed for perforated appendicitis.…”
Section: Discussionmentioning
confidence: 99%